Occurrence of Quesada gigas on Schizolobium amazonicum trees in Maranhão and Pará States, Brazil - Zanuncio, José Cola; Pereira, Fabrício Fagundes; Zanuncio, Teresinha Vinha; Martinelli, Nilza Maria [UNESP]; Pinon, Tobias Baruc Moreira; Guimarães, Edylene Marota (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2004)
Há relatos sobre a infestação de Quesada gigas Olivier (Hemiptera: Cicadidae) em paricá Schizolobium amazonicum (Huber) Ducken (Fabales: Fabaceae) nos municípios de Itinga, Estado do Maranhão e Paragominas, Estado do Pará. Observaram-se ninfas nas raízes e adultos e exúvias nos troncos da planta. Orifícios no solo, de saída de ninfas móveis dessa cigarra também foram verificados. A ocorrência de Q. gigas em S. amazonicum mostra o potencial de danos da espécie e a necessidade de se desenvolver programas de manejo integrado de espécies desse grupo, principalmente Q. gigas, em áreas reflorestadas com paricá.

An infestation of Quesada gigas Olivier (Hemiptera: Cicadidae) on paricá Schizolobium amazonicum (Huber) Ducken (Fabales: Fabaceae) was reported in the Municipalities of Itinga, Maranhão State and Paragominas, Pará State. Nymphs of this insect on roots and adults and exuvias on trunks of the plant were observed. Exit holes of nymphs in the soil were also observed. The occurrence of Q. gigas on S. amazonicum shows the damage potential of this species and the necessity of developing integrated management programs for species of this group, specially in reforested areas with paricá.
Ocorrência de Quesada gigas em Schizolobium amazonicum em municípios do Maranhão e do Pará
Keywords: Cicadidae; cigarras; reflorestamento; pragas de solo; paricá; Cicadidae; Cicada; reforestation; soil pest; paricá